ASSESSING THE POSSIBILITY OF USING OF ZAZHOGINSKY DEPOSIT SHUNGITE IN METALLURGY - A. S. Panasyugin; A. R. Ziganov; S. V. Grigoriev; Z. N. Chipurko; L. M. Guzova (Литьë и металлургия, 2013)
By electron microscopy, electron microprobe, X-ray diffraction and elemental analyzes carried out the research on the distribution of chemical elements over the surface of schungite, the most typical areas of distribution of crystallographic phases on the surface of samples and their relationship.